Strata Data Conference : San Jose 2018 (O'Reilly Media, 2018)
"This video compilation provides a complete recording of the conference's keynote speeches, tutorials, and sessions, including unfettered access to the exclusive Strata Business Summit ('the missing MBA for data-driven business') and its Executive Briefings on how to turn data and algorithms into business advantage."--Resource description page